PENGARUH MEWARNAI GAMBAR TERHADAP TINGKAT KECEMASAN HOSPITALISASI PADA ANAK PRA SEKOLAH DI RS NURUL HASANAH KUTACANE TAHUN 2021 - Yusnika Damayanti (Jurnal Maternitas Kebidanan, 2021)
The family has a health duty whose purpose is to prevent the occurrence of health problems and care for sick family members. There are five health tasks that must be done by the family dengan well. The implementation of this family health task is inseparable from the cultural factors owned by the family, such as the Minangkabau tribe who adhere to the patrilineal system. This research aims to identify the implementation of family health tasks in the Minangkabau tribe in Nogo Rejo Village of Galang Subdistrict. Research design is descriptive. Sampling with purposive sampling technique. A sample of 46 people consisted of 28 male respondents and 18 female respondents. The study was conducted from May 17 to July 12, 2021. Data collection is done using a questionnaire of family health tasks that includes demographic data and family health tasks. Then the data obtained is processed using descriptive analysis to determine the distribution of frequencies and percentages. The results showed that almost two-thirds (2/3) of respondents carried out family health duties in the Minangkabau tribe with a good category (63.04%). The conclusion of this study shows that implementing family health duties in the Minangkabau tribe belongs to the category of good (63.04%).